Role of ORAI calcium release-activated calcium modulator 1 (ORAI1) on neutrophil extracellular trap formation in dairy cows with subclinical hypocalcemia - Zhang, Bingbing; Ma, Xinru; Loor, Juan J.; Jiang, Qianming; Guo, Han; Zhang, Wei; Li, Ming; Lv, Xinquan; Yin, Yufeng; Wen, Jianan; Wang, Jingjing; Xu, Chuang; et al. (Journal of dairy science, 2022)
Hypocalcemia in dairy cows is associated with decreased neutrophil phagocytosis, adhesion capacity, migration, and reactive oxygen species (ROS) production through alterations in ORAI calcium release-activated calcium modulator 1 (ORAI1). Neutrophils can resist the invasion of pathogenic microorganisms by releasing neutrophil extracellular traps (NET). However, the mechanisms controlling NET formation during hypocalcemia are unknown. To address the role of ORAI1 in NET formation, neutrophils were isolated at 2 d postcalving from lactating Holstein dairy cows (n = 10 per group) diagnosed as clinically healthy (control) or with plasma concentrations of Ca2+ <2.0 mmol/L as a criterion for diagnosing subclinical hypocalcemia (SCH). A series of ex vivo experiments were conducted as follows: first, neutrophils isolated from both groups of cows were treated with phorbol 12-myristate 13-acetate (PMA) to stimulate NET formation; second, neutrophils from control and SCH were pretreated with or without the ROS scavenger N-acetylcysteine (NAC), the sarcoendoplasmic Ca2+ ATPase inhibitor thapsigargin, or ORAI1 blocker 2APB and then treated with PMA to stimulate NET formation; and third, neutrophils were transfected with small interfering (si)ORAI1 or nontarget siRNA (siNEG) and then stimulated with PMA to induce formation of NET. A one-way ANOVA was used for statistical analysis of individual experiments. In the first experiment, neutrophils from SCH cows formed NET with fewer DNA filaments, more diffused nuclei, and reduced translocation of myeloperoxidase (MPO) and neutrophil elastase (NE) to the nucleus. Neutrophils from SCH cows stimulated with PMA had a lower mitochondrial permeability, the state of mitochondrial permeability transition pore was open, ROS production was lower and there was increased mitochondrial damage. In the second experiment, in both control and SCH-PMA stimulated neutrophils, exogenous NAC decreased NET formation (assessed via Hoechst 33342 dye; Beyotime). Furthermore, following the challenge with PMA, thapsigargin increased NET formation and ROS production, but blocking ORAI1 with 2APB decreased NADPH oxidase activation, ROS production, and NET formation. In the third experiment, neutrophils transfected with siORAI1 before stimulation with PMA had lower intracellular concentrations of Ca2+, NET formation, and ROS production. Overall, the data indicated that SCH reduces NET formation in neutrophils partly due to damaged mitochondria. The reduction in ORAI1 abundance in neutrophils of dairy cows with hypocalcemia also decreases ROS production.